دور التحالفات الاستراتيجية مع مؤسسات التأمين في تحسين أداء البنوك: محاولة لتحليل أداء البنوك الجزائرية باستخدام نموذج Scp - حيمر, مريم; دبلة, فاتح (جامعة الوادي - University of Eloued, 2021)
This study is based on analyzing the performance of the banking sector, using an analysis tool that is closer to the economic reality through the model of the industrial economy structure-behaviourperformance SCP, by interpreting the relationship between the elements of this model in the banking sector in Algeria in light of the strategic alliances of banks with Insurance institutions. Some of the study results were against the first hypothesis of the structure-behaviorperformance model
Le rôle des alliances stratégiques avec les institutions d'assurance dans l'amélioration de la performance des banques : une tentative d'analyse de la performance des banques algériennes à l'aide du modèle SCP
مقال
Keywords: البنوك-التحالفات الاستراتيجية-نموذج scp – الأداء- بنك التأمين.; Banques-alliances stratégiques-le paradigme SCP-performance-assurance banque.